The Application of Physiotherapy in Urinary Incontinence - Małgorzata Wójcik; Katarzyna Placek; Tomasz Goździewicz; Katarzyna Plagens-Rotman; Piotr Merks; Małgorzata Mizgier; Dawid Luwański; Magdalena Pisarska-Krawczyk; Witold Kędzia; Grażyna Jarząbek-Bielecka (IMR Press, 2023)
Objective: The problem of urinary incontinence affects half of the adult female population, impacting adversely on their comfort of life and significantly hindering ordinary life activities (laughing, sneezing, coughing, physical activity); it also affects the quality of their sexual life. Physiotherapy is an increasingly common method for the conservative treatment of genital static disorders and stress urinary incontinence. Mechanism: In this article, the authors consider the following aspects: the use of various physiotherapy interventions as adjunctive treatment for urinary incontinence. The authors reviewed the literature databases in PubMed, Medline and Embase to identify links between the applied physiotherapeutic treatment and its effectiveness. Findings in Brief: The applied physiotherapeutic treatments and their effectiveness in urinary incontinence are presented. Conclusions: Physiotherapy treatments are effective and supportive of the treatment process in women of all age ranges with urinary incontinence, thus improving their quality of life.